Magneto Thermosolutal Convection in a Compressible Viscoelastic Fluid - Pardeep Kumar (Newinera Publisher, 2022)
In the presence of a magnetic field, a thermosolutal convection is postulated to occur in a compressible Rivlin-Ericksen viscoelastic fluid in a porous media. The dispersion relation is found by using the linear stability theory and the normal mode analysis approach, respectively. In the scenario of stationary convection, it was discovered that compressibility, magnetic fields, and steady solute gradients all serve to delay the beginning of the convection process, but medium permeability serves to speed up the beginning of the convection process. In addition to this, it has been discovered that the system is reliable for [equation not detected by OJS] and under the condition [equation not detected by OJS]. The system goes into an unstable state. Overstability has also been looked at from the perspective of a scenario in which sufficient circumstances are met to rule out the possibility of the phenomenon occurring. It has been discovered that the steady gradient of the solute and the magnetic field both induce oscillatory modes into the system.